An experimental study on the thermal characteristics of the Cell-To-Pack system. (15th July 2021) - Wang, Huaibin; Wang, Shuyu; Feng, Xuning; Zhang, Xuan; Dai, Kangwei; Sheng, Jun; Zhao, Zhenyang; Du, Zhiming; Zhang, Zelin; Shen, Kai; Xu, Chengshan; Wang, Qinzheng; et al.
Abstract: The development of electric vehicle batteries has resulted in high energy density battery pack. Cell-to-Pack (CTP) omits the cell module assembly, can reduce battery pack parts by 40%, improve the battery pack volume utilization rate by 15%–20%. However, the thermal characteristics of CTP under full operating conditions has yet to be verified, the CTP temperature calibration cycle under full working condition is time-consuming, and little analysis has been conducted on CTP internal temperature differentials and heat flow. The present study aims to thermal characteristics of CTP. Results show that CTP temperature calibration based on a thermal resistance grid can realize internal temperature reconstruction, optimum temperature arrangement, and shorten the calibration period by more than 60%. In addition, higher ambient temperatures can increase the maximum temperature of the jelly rolls in CTP cells, while lower ambient temperature can lead to larger differences in jelly roll temperature within a cell; and high-speed driving and fast charging can lead to the highest temperature increase rates under different working conditions up to 0.05 °C s −1 .70% of the heat generated during cell discharge is used for self-heating, and the heat dissipation of liquid cooled plate is the main heat dissipation channel. Highlights: The thermal characteristics of the Cell-To-Pack system are described. The location of the original BMS temperature acquisition point was optimized. Initial SOC and ambient temperature affects cell temperature under 4C charging. Driving at a constant speed of 100 km/h on a 6% ramp caused maximum temperature. 70% of the total heat generated during charging was used to heat the cell itself.